SURVEILLANCE MISSION OPTIMIZATION FOR UAV MALE XM-2 (CASE STUDY: MAXIMUM FLIGHT TIME PROBLEM) - Ernest Halasan Sirait, Boris
Surveillance mission flight scenario optimization of the Unmanned Aerial Vehicle Medium Altitude Long Endurance is required to assure Design Requirement fulfillment. UAV MALE mission optimizations is focused on how to define the best mission profile to maximize total flight time in executing surveillance mission. In this study, Conventional method with integral performance analysis is conducted to observe the effect of aircraft speed, flight altitude and aircraft attitude on fuel consumption in executing each flight phase on surveillance mission. The first flight phase analysis is climb phase; in this phase, aircraft speed is varied to obtain optimum climb speed. Optimum climb speed is achieved by choosing the speed that can obtain minimum time to climb and minimum fuel to climb. The second flight phase analysis is cruise phase; in this phase, optimum cruise speed is achieved by choosing the speed that can obtain level flight maneuver with minimum power for all cruise altitude. The third flight phase analysis is loiter phase; in this phase, optimum loiter flight scenario is achieved by varying the speed, bank angle, turn radius and loiter method (constant angle of attack or constant bank angle). The fourth flight phase analysis is descend phase; in this phase, optimum flight scenario for descend phase is achieved by varying the speed and rate of descend that can obtain maximum total flight time. After the analysis for each flight phase is conducted, then surveillance flight mission analysis which can achieve 24 hours loiter flight at the horizontal distance of 250 Km from base station can be conducted. For that mission, there are two schemes that is analyzed in this study, which the first scheme is using constant speed throughout mission and the second scheme is using optimum speed for each flight phase. The analysis on each flight phase results in optimum climb speed 67 KEAS, optimum cruise and loiter speed 67 KEAS, optimum loiter method is constant bank angle with optimum bank angle 100 and maximum bank angle which can obtain 24 hours loiter flight is 280, and descend speed 70 KEAS with rate of descend 500 ft/min. Afterward, the analysis for all flight phase at once results in optimum constant speed 62 KEAS throughout mission. Flight scheme for optimum speeds on each flight phase results in total flight time 28 hours and 46 minutes, while flight scheme for optimum constant speed throughout mission results in total flight time 30 hours.